PENGARUH INTENSITAS MODAL DAN STRATEGI BISNIS TERHADAP AGRESIVITAS PAJAK (Studi Empiris perusahaan manufaktur sektor industri barang konsumsi yang terdaftar di Bursa Efek Indonesia tahun 2019-2022) - Ayem, Sri; Andriyani, Indah Novita (FORPIM PTKIS ZONA TAPAL KUDA, 2024)
Tax aggressiveness can be influenced by various factors. This study aims to examine the effect of capital intensity and business strategy on tax aggressiveness. The population used in this study are manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange in 2019-2022. The type of data used is secondary data. The research sample used purposive sampling with the number of manufacturing companies sampled in this study as many as 20 companies and obtained 40 annual financial report data. This study uses multiple linear analysis. The results showed that capital intensity has a positive effect on tax aggressiveness and business strategy has a negative effect on tax aggressiveness. The results of this study can be used for taxpayers and related agencies in carrying out their duties and responsibilities for work, creating an honest and good work environment so that tax aggressiveness activities do not occur.